Analisis Teknik Penulisan Laporan Praktikum Biokimia Mahasiswa Prodi Biologi Semester 2 ITS NU Pasuruan - Sofiyah, Fina; Rokhimah, Ainur; Kamelia, Nisaul; Rizqiyah, Sila (Jurnal Likhitaprajna, 2023)
This study aims to describe whether the causes of difficulty in writing biochemistry practicum students of ITSNU Pasuruan semester 2 class 22d-A are related to the format of student understanding reports. The research method used is quantitative research where in this research the data collection techniques used include interviews and documentation. This research was conducted at ITSNU Pasuruan in April-May 2023. The results of this study concluded that 58.1% of students knew what a biochemistry report was, 48.4% found it easy to make a biochemistry report, 61.3% were still unsure whether the lecturer had a format separately, 64.5% of students were able to explain/define what had been done in the laboratory into practicum reports, and 61.3% of students were able to manage practicum reports with Ms. word.